Analysis of three-dimensional biofilms on different material surfaces. (20th May 2020) - Schiebel, Juliane; Noack, Jonas; Rödiger, Stefan; Kammel, Anne; Menzel, Friederike; Schwibbert, Karin; Weise, Matthias; Weiss, Romano; Böhm, Alexander; Nitschke, Jörg; Elimport, Alexey; Roggenbuck, Dirk; et al.
Abstract : We developed a combination of an automated epifluorescence microscopy system with the analysis software Open-Biofilm-Altimeter for semi-quantitative analysis of three-dimensional biofilms. Abstract : Biofilms cause complications and high costs in both industry and medicine. Of particular interest are bacterial infections of prosthetic materials, which usually cannot be eliminated due to the high antibiotic resistance known for bacteria forming biofilms. The search for new materials and coatings with lower colonization potential and antibacterial activity is of great importance to reduce biofilm formation. However, there is no standardized procedure to examine the colonization characteristics of bacteria in the biofilm state in situ . Here, we describe an automated epifluorescence microscopy system for the semi-quantitative analysis of three-dimensional (3D) biofilms on various surfaces. To analyze adherent bacteria, three materials (glass, steel and titanium) were incubated with bacteria in a flow chamber system. After fluorescence staining of the bacteria, automated image capturing, quantification of the bacteria, measurement of the colonized area and determination of the 3D biofilm height were carried out by using novel software. Furthermore, the materials were examined for their surface topography using white light scanning interferometry. Titanium compared to glass showed a significantly higher number of adherent bacteria. We argue that this was due to the higher microroughness of titanium. The colonized area was in accordance with the number of adherent bacteria and was also significantly larger on titanium coupons compared to glass. Maximum 3D biofilm height on glass coupons was significantly lower compared to the ones on steel and titanium. This novel method enables the standardized, automated investigation of the colonization with bacteria on different materials. This approach can considerably support the characterization of new material surfaces and their innovative coatings by analyzing the amount of attached bacteria and thickness of biofilms in situ and eliminates the need of conventional cultivation.